Fascinating or dull? Female students’ attitudes towards STEM subjects and careers - Lane, Ciara; Kaya-Capocci, Sila; Kelly, Regina; O’Connell, Tracey; Goos, Merrilyn (Frontiers in Psychology, 2022)
Internationally, the need to advance science, technology, engineering and mathematics (STEM) education is recognized as being vital for meeting social and economic challenges and developing a scientifically, mathematically, and technologically literate citizenry. In many countries, however, there are gender differences in the participation and achievement of girls and women in STEM education and STEM careers, usually to the disadvantage of females. This paper aims to identify challenges to female students’ participation in STEM both at post-primary (secondary school) level and beyond in the Irish context. The research questions we aim to address in this paper are: (1) what are student attitudes towards science, technology, engineering and mathematics as measured through interest and perceived ability in STEM, students’ valuing of STEM and students’ commitment to STEM? and (2) what gender differences occur regarding students’ attitudes to science, technology, engineering and mathematics? A survey was completed by 308 post-primary students in Ireland as part of a one-year research project titled “STEMChAT: Women as catalysts for change in STEM education”. Data analysis compiled descriptive statistics, including response frequencies and percentages and median and interquartile range values, and compared gender differences in survey responses using the Kruskal-Wallis H Test. Results indicated that female students had significantly more positive attitudes to science compared to males while in comparison, males had significantly more positive responses to mathematics compared to females. Challenges regarding access to and understanding of STEM in the context of post-primary education are discussed.